2006
DOI: 10.1073/pnas.0603620103
|View full text |Cite
|
Sign up to set email alerts
|

Drosophila Rtf1 functions in histone methylation, gene expression, and Notch signaling

Abstract: The Rtf1 subunit of the Paf1 complex is required for proper monoubiquitination of histone H2B and methylation of histone H3 on lysines 4 (H3K4) and 79 in yeast Saccharomyces cerevisiae. Using RNAi, we examined the role of Rtf1 in histone methylation and gene expression in Drosophila melanogaster. We show that Drosophila Rtf1 (dRtf1) is required for proper gene expression and development. Furthermore, we show that RNAi-mediated reduction of dRtf1 results in a reduction in histone H3K4 trimethylation levels on b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
72
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(76 citation statements)
references
References 29 publications
4
72
0
Order By: Relevance
“…Paf1C associates with RNA pol II from the 5′ end of a gene to the poly(A) site (22, 23); interacts functionally and physically with the transcription elongation factors Spt4-Spt5/DSIF, Spt16-Pob3/FACT, and TFIIS (8,(24)(25)(26)(27); regulates the phosphorylation state of RNA pol II (28, 29); and is required for proper 3′ end formation of certain transcripts (30-32). Important to this study, deletion of RTF1 from yeast cells causes dramatic reductions in H2B K123 ubiquitylation and H3 K4 and K79 methylation (33-36), and this role in histone modification, like other Paf1C functions, is conserved in higher eukaryotes (37)(38)(39)(40).The mechanisms by which Paf1C promotes histone modifications have yet to be elucidated. Deletion of RTF1, CTR9, or PAF1 reduces the occupancies of Rad6 and Set1/COMPASS on coding regions (33,35,41), and purified Paf1C interacts with Bre1 in vitro (42,43), suggesting that Paf1C serves as a platform for recruiting histone-modifying enzymes to RNA pol II during elongation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Paf1C associates with RNA pol II from the 5′ end of a gene to the poly(A) site (22, 23); interacts functionally and physically with the transcription elongation factors Spt4-Spt5/DSIF, Spt16-Pob3/FACT, and TFIIS (8,(24)(25)(26)(27); regulates the phosphorylation state of RNA pol II (28, 29); and is required for proper 3′ end formation of certain transcripts (30-32). Important to this study, deletion of RTF1 from yeast cells causes dramatic reductions in H2B K123 ubiquitylation and H3 K4 and K79 methylation (33-36), and this role in histone modification, like other Paf1C functions, is conserved in higher eukaryotes (37)(38)(39)(40).The mechanisms by which Paf1C promotes histone modifications have yet to be elucidated. Deletion of RTF1, CTR9, or PAF1 reduces the occupancies of Rad6 and Set1/COMPASS on coding regions (33,35,41), and purified Paf1C interacts with Bre1 in vitro (42,43), suggesting that Paf1C serves as a platform for recruiting histone-modifying enzymes to RNA pol II during elongation.…”
mentioning
confidence: 99%
“…Paf1C associates with RNA pol II from the 5′ end of a gene to the poly(A) site (22, 23); interacts functionally and physically with the transcription elongation factors Spt4-Spt5/DSIF, Spt16-Pob3/FACT, and TFIIS (8,(24)(25)(26)(27); regulates the phosphorylation state of RNA pol II (28, 29); and is required for proper 3′ end formation of certain transcripts (30-32). Important to this study, deletion of RTF1 from yeast cells causes dramatic reductions in H2B K123 ubiquitylation and H3 K4 and K79 methylation (33-36), and this role in histone modification, like other Paf1C functions, is conserved in higher eukaryotes (37)(38)(39)(40).…”
mentioning
confidence: 99%
“…26 It is also of interest to note that knockdown of the histone chaperones ASF1 and NAP1 in insect cells results in derepression of Notch-target genes, and both chaperones physically interact with the H3K4me2/3 demethylase LID/KDM5. 27,28 Depletion of either histone chaperone results in an increase in H3K4me3 at the promoters of Notch target genes, while global levels of this methylated histone were unaffected (Fig.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%
“…Moreover, Drosophila Rtf1 (Restores TBP function 1) was identified as an essential protein during development and found to be involved in the histone modification for H3K4 and H2b, suggesting that its function is conserved from yeast to human. The same study showed that dRtf1 affects the transcription level of Notch target genes [235]. Also, dpaf-1 is an essential gene and involves in methylation of H3K4 [246].…”
Section: The Paf1 Complex In Drosophilamentioning
confidence: 89%
“…For instance, several studies showed that Paf1C promote histone trimethylation of H3K4 and H3K36, and ubiquitination of H2BK123; Paf1C is involved in chromatin remodeling, transcription elongation and it mediates transcriptional termination for RNA polymerase II [224,230]. Inanition, several studies have suggested relations between Wnt or Notch signaling and different components of Paf1C [233][234][235][236]. Further, some of the Paf1C components e.g., Ctr9 are identified as a tumor suppressor factor in various organisms especially in human [232,[237][238][239][240][241].…”
Section: Mapping By Wgsmentioning
confidence: 99%